2016
DOI: 10.1037/npe0000060
|View full text |Cite
|
Sign up to set email alerts
|

A mind for money: Dynamic mindset effects on smart risk taking.

Abstract: Identifying the optimal level of risk taking is an important skill to maximize gains. We tested the potential of the deliberative and implemental mindsets to optimize risk taking to maximize profits, using an incentivized ring toss game. Participants in an implemental mindset showed a dynamic risk-taking pattern and earned higher profits than did participants in the deliberative mindset and the control condition. Also, monetary incentives motivated participants in the deliberative mindset to overcome low expec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…Further, individuals in a deliberative mindset are supposed to have realistic expectancy-value considerations and realistic evaluations of their own skills (Heckhausen & Gollwitzer, 1987;Gollwitzer, 1990). In line with these expectations, previous research showed that the deliberative mindset can reduce risk-seeking behavior (Dörflinger, Martiny-Hünger, & Gollwitzer, 2017), lead to moderate expectancies about performance in risk choice tasks (Rahn, Jaudas, & Achtziger, 2016b), and result in low levels of overconfidence on general knowledge (Hügelschäfer & Achtziger, 2014).…”
Section: Deliberative and Implemental Mindsetsmentioning
confidence: 62%
See 2 more Smart Citations
“…Further, individuals in a deliberative mindset are supposed to have realistic expectancy-value considerations and realistic evaluations of their own skills (Heckhausen & Gollwitzer, 1987;Gollwitzer, 1990). In line with these expectations, previous research showed that the deliberative mindset can reduce risk-seeking behavior (Dörflinger, Martiny-Hünger, & Gollwitzer, 2017), lead to moderate expectancies about performance in risk choice tasks (Rahn, Jaudas, & Achtziger, 2016b), and result in low levels of overconfidence on general knowledge (Hügelschäfer & Achtziger, 2014).…”
Section: Deliberative and Implemental Mindsetsmentioning
confidence: 62%
“…These earlier results indicated that information search was more intense and information processing more thorough in the implemental mindset compared to the deliberative mindset. Together with other processes that were instigated by the implemental mindset (e.g., more confidence in one's cognitive skills: Hügelschäfer & Achtziger, ; the induction of a learning mode when making decisions under uncertainty with success/failure feedback: Rahn et al, ; higher self‐esteem and optimism: Taylor & Gollwitzer, ), decision processes were supported in a way that they increased decision performance. Hence, when facing conflicts between Bayes' rule and the reinforcement heuristic, participants in an implemental mindset did better in integrating all available information according to Bayes’ rule and did not rely on a subset of information (win/loss feedback) only what would have resulted in high rates of reinforcement errors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, Harmon‐Jones and Harmon‐Jones () revealed that the chosen option was more positively evaluated in the implemental mindset than in the deliberative mindset. Other examples of mindset effects include less overconfidence in the deliberative mindset (Hügelschäfer & Achtziger, ) and more goal persistence in the implemental mindset (V. Brandstätter & Frank, ; Rahn, Jaudas, & Achtziger, ).…”
Section: Mindsets Incentives and Decisions Under Riskmentioning
confidence: 99%
“…Some studies have already used the deliberative and implemental mindsets to explore the effects of motivational and volitional processes on decisions (V. Brandstätter, Giesinger, Job, & Frank, 2015;Büttner et al, 2014;Hügelschäfer & Achtziger, 2014;Keller & Gollwitzer, 2017;Li, Hügelschäfer, & Achtziger, 2019;Rahn et al, 2016a;Rahn, Jaudas, & Achtziger, 2016b). For instance, Li et al (2019) observed that rational decision making was increased in the implemental mindset compared with a baseline and a deliberative mindset condition.…”
Section: Mindsets Incentives and Decisions Under Riskmentioning
confidence: 99%